PENGARUH BRAND FAMILIARITY DAN PERCEIVED QUALITY TERHADAP BRAND CREDIBILITY - Ray Fauzan; Tantio Dipo Priantono; Lingga Yuliana (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This study intends to examine how Brand Credibility is influenced by Brand Familiarity and Perceived Quality. Purposive sampling is the sampling method used in the research, which employs a quantitative descriptive methodology. Participants in this study who used Kahf skincare products were respondents. The data used are first-hand records. The main information was gathered from 75 respondents who used the Kahf brand and received questionnaires using a Google form. Partial Least Square (PLS) has been implemented in the data analysis technique with the Smart PLS analysis tool version 3.3.9. The findings refuted the initial idea that brand familiarity affects brand credibility. The second premise holds that perceived quality affects the credibility of a brand. The third theory is that brand familiarity affects how quality is perceived.